Uniportal thoracoscopic lobectomy for intralobar pulmonary sequestration. Issue 1 (December 2016) - Sihoe, Alan; Luo, Qigang; Shao, Guangqiang; Li, Yue; Li, Jinglong; Pang, Dazhi
Abstract Background Pulmonary sequestration is an uncommon congenital condition for which surgical resection is usually indicated – either via open thoracotomy or conventional multi-port Video-Assisted Thoracoscopic Surgery (VATS). Of the two types of sequestration, intralobar sequestration is technically more challenging to resect. Case Presentation We report the management of a 34 year old male patient with a long history of respiratory symptoms, and an extensively diseased right lower lobe. A diagnosis of sequestration was confirmed by CT scanning, showing three separate anomalous feeding vessels arising from the abdominal aorta. A right lower lobectomy using a Uniportal VATS approach was performed, and the patient discharged home on the fourth post-operative day. Conclusion This is the first report to our knowledge demonstrating the safety and feasibility of the Uniportal approach for the resection of a relatively challenging intralobar sequestration.